Microbial Toxins (Toxinology,, 2018)
This volume provides an overview of microbial toxins from diverse bacterial and fungal origins. These molecules, produced by various species and consisting of protein or small organic molecules, can play a pivotal role in pathogenesis of plants, animals, and humans that in turn can lead to the survival/dissemination of the host microbe. Many of these microbes, due to their toxins, impact our society from a health and economic perspective. In particular, this volume address the diverse niches of these organisms focused upon their associated toxins. The structures, functions, and genetics of toxins will be addressed. Besides the ill-effects elicited by these toxins, it must be noted that there is immense potential for turning some of these harmful molecules into useful tools as specific probes (of receptors), novel drugs or drug-conjugates for the treatment of various diseases, and immunomodulating agents for targeted vaccine delivery for research and unique medicines. Recent progress in bacterial genome mapping and establishment of three-dimensional crystal structures of several bacterial toxins provides a deeper knowledge and greater understanding of structure-function relationships. Moreover, the emergence of some bacteria (i.e., Bacillus anthracis, Burkholderia pseudomallei, Staphylococcus aureus), and their toxins, as biological weapons also necessitates a thorough understanding of these agents, their pathophysiology, and development of countermeasures. This volume will also be a common resource for researchers interested in many other medically-relevant microorganisms, and their toxins, that include Clostridium botulinum, C. difficile, C. perfringens, C. tetani, Escherichia coli, Helicobacter pylori, and Listeria monocytogenes. Recent studies have correlated the effect of global warming and climate change as a trigger for natural disasters and impact on human health via emergence of various vector-borne and infectious diseases caused by toxin-producing microbes. The 2003 Institute of Medicine (IOM) report, "Microbial Threats to Health," identified the influence of changing ecosystem on the emergence and spread of infectious diseases and economic development of specific regions of the world. This current handbook is a major reference work on microbial toxins written by a panel of International experts and organized into 24 chapters.